2021
DOI: 10.3389/fnagi.2021.761010
|View full text |Cite
|
Sign up to set email alerts
|

18F-THK5351 Positron Emission Tomography Imaging in Neurodegenerative Tauopathies

Abstract: Introduction: We aimed to determine whether in vivo tau deposits and monoamine oxidase B (MAO-B) detection using 18F-THK5351 positron emission tomography (PET) can assist in the differential distribution in patients with corticobasal syndrome (CBS), progressive supranuclear palsy (PSP), and Alzheimer’s disease (AD) and whether 18F-THK5351 retention of lesion sites in CBS and PSP can correlate with clinical parameters.Methods:18F-THK5351 PET was performed in 35 participants, including 7, 9, and 10 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“… 152 The THK-5351 retention pattern was different among AD, PSP and CBS, but none of the patients had autopsy confirmation. 153 The underlying pathology of CBS patients remained unclear; therefore, the usefulness of THK-5351 in differentiating the pathology of CBS, particularly CBD or PSP, needs to be elucidated.…”
Section: Fluid and Imaging Biomarkers For Cbsmentioning
confidence: 99%
“… 152 The THK-5351 retention pattern was different among AD, PSP and CBS, but none of the patients had autopsy confirmation. 153 The underlying pathology of CBS patients remained unclear; therefore, the usefulness of THK-5351 in differentiating the pathology of CBS, particularly CBD or PSP, needs to be elucidated.…”
Section: Fluid and Imaging Biomarkers For Cbsmentioning
confidence: 99%
“…Although there were a lot of limitations to interpret [ 18 F]THK-5351 PET images on the biological point of view due to the lack of selectivity, many clinical studies using [ 18 F]THK-5351 imply the association of reactive astrogliosis in various conditions. Clinical PET studies demonstrated high and different distribution of [ 18 F]THK-5351 retention in sites susceptible to tau deposition in AD and non-AD conditions such as Parkinsonian syndromes ( Harada et al, 2016 ; Kikuchi et al, 2016 ; Brendel et al, 2017 ; Ishiki et al, 2017 ; Shimizu et al, 2018 ; Schonecker et al, 2019 ; Hsu et al, 2020 ; Ezura et al, 2021 ; Figure 2 ). Furthermore, [ 18 F]THK-5351 retention mirrors glucose hypometabolism measured with [ 18 F]fluorodeoxyglucose in the focal variants of AD ( Kang et al, 2017 ; Park et al, 2021 ).…”
Section: Clinical Studies Using Positron Emission Tomography Radiotra...mentioning
confidence: 99%
“…Nihashi et al (2021) suggested that the quantity of [ 18 F]THK5351 uptake in the brain of AD patients inversely correlated with hippocampal volume and neuropsychological assessment, implying that [ 18 F]THK5351 may be a candidate for monitoring AD disease progression. Ezura et al (2021) compared differential binding of [ 18 F]THK5351 to different tauopathies and found that high [ 18 F]THK5351 uptake was detected in the precentral and postcentral gyri of CBD patients, in the midbrain of PSP patients and in the parahippocampal gyri of AD patients compared to healthy controls, clearly distinguishing different tauopathies. In vivo imaging using [ 11 C]PBB3 showed the detection of tau inclusions in the brain stem of PS19 and cortical and hippocampal regions of the rTg4510 mouse model of FTD (Maruyama et al, 2013;Ishikawa et al, 2018;Ni et al, 2018;Vagenknecht et al, 2022).…”
Section: In Vivomentioning
confidence: 99%